Language effects in international testing: the case of PISA 2006 science items - Masri, Y; Baird, J; Graesser, A (Taylor and Francis (Routledge), 2016)
We investigate the extent to which language versions (English, French and Arabic) of the same science test are comparable in terms of item difficulty and demands. We argue that language is an inextricable part of the scientific literacy construct, be it intended or not by the examiner. This argument has considerable implications on methodologies used to address the equivalence of multiple language versions of the same assessment, including in the context of international assessment where cross-cultural fairness is a concern. We also argue that none of the available statistical or qualitative techniques are capable of teasing out the language variable and neutralising its potential effects on item difficulty and demands. Exploring the use of automated text analysis tools at the quality control stage may be successful in addressing some of these challenges.